COST OF COMPLEXITY AND THE REFORM IN THE POWER SECTOR (AVOIDING CHAOS IN THE PATH TO AN OPTIMAL MARKET STRUCTURE) - Ionuț PURICA (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2020)
The reform of a one player power sector (i.e. a natural monopoly) into a multiple players’ power market brings to the clients not only the benefits of competition but also the costs of complexity. In between the two, an optimal number of players is found in the market corresponding to the minimum price of power to the clients. Considering time as the third dimension, the optimum curve becomes a potential surface on which the evolution of the market entities is seen as oscillations along the valley of minimum price. Every oscillation triggers a price burst which is detrimental to the clients. To avoid this, the role of the regulator is better defined in the sense of smoothing the transition from monopoly to market. The example of the US power sector evolution is relevant here. In the above approach long range competition resulting from the future opening of power markets in Europe, or from the penetration, 70 years ago, of the interconnection technology in USA, is compared with the short range (local) competition. Finally, the price limits are determined which ensure that (i) the new entrants on the market are not eliminated and, (ii) that the market avoids oscillations which may drastically shock a non-resilient economy. A case study calculation is done for Romania and a method is proposed where the cost of complexity is assessed based on the ratio of traded energy to consumed one i.e. more traded energy means that the price increases with every transaction that is not bringing the energy to the consumer but to other traders. An example Is presented for the present open market of Romania.